2020
DOI: 10.1111/1462-2920.15227
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic processes shape the biogeographic variations in core bacterial communities between aerial and belowground compartments of common bean

Abstract: Although studies of biogeography in soil bacterial communities have attracted considerable attention, the generality of these patterns along with assembly processes and underlying drivers is poorly understood in the inner tissues of plants. Plant tissues provide unique ecological habitats for microorganisms, which play an essential role in plant performance. Here, we compared core bacterial communities among five soil–plant associated compartments of common bean across five sampling sites in China. Neutral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 77 publications
6
4
0
Order By: Relevance
“…In the present study, we found robust evidence for DDRs of bacterial communities in both bulk and rhizosphere sediment samples across the plain region (Figure 3), which is consistent with previous observations of different terrestrial ecosystems (Fan et al, 2017; Jiao et al, 2020; Liu et al, 2020; Wang et al, 2017; Zhang et al, 2018b). Furthermore, based on null model theory, we found that deterministic processes, especially variable selection, had dominant roles in driving the bacterial community assembly of lakeshore bulk sediment (Figure 4a).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found robust evidence for DDRs of bacterial communities in both bulk and rhizosphere sediment samples across the plain region (Figure 3), which is consistent with previous observations of different terrestrial ecosystems (Fan et al, 2017; Jiao et al, 2020; Liu et al, 2020; Wang et al, 2017; Zhang et al, 2018b). Furthermore, based on null model theory, we found that deterministic processes, especially variable selection, had dominant roles in driving the bacterial community assembly of lakeshore bulk sediment (Figure 4a).…”
Section: Discussionsupporting
confidence: 92%
“…The DDRs of the microbiotas in the present study were confirmed by the results of (partial) Mantel tests, and displayed similar patterns to those of other studies (Jiao and Lu, 2020;Liu et al, 2021). Moreover, the environmental factors were significantly correlated with the microbial communities in the BS and RS, which has also been found in previous studies (Xiong et al, 2012;Zhang et al, 2018).…”
Section: Effects Of Multiple Factors On the Distributions Of Root-associated Microbiotassupporting
confidence: 91%
“…The geography had the greatest direct effects on the bacterial communities in RS, which is in accordance with the results of the above Mantel tests (Table 4), and has been illustrated in other studies that have discussed the geographic distance has a greater impact on rhizosphere microbiotas due to the combined influences of plant root exudates (Xiong et al, 2012;Liu et al, 2021). It has become apparent that the biogeographic distance decay patterns of microbiotas in the root endosphere are usually not obvious (Zhang et al, 2018).…”
Section: Integrated Modulations Of Licorice Root Secondary Metabolitessupporting
confidence: 88%
“…Soil compartments separated the rhizosphere bacterial community (α- and β- diversity) from the bulk soil under either planting pattern. Previous studies concerning other plant microbiomes also confirmed this partition ( Santhanam et al, 2015 ; Dombrowski et al, 2017 ; Fan et al, 2017 ; Liu et al, 2020 ). The rhizosphere is a highly dynamic environment that is the primary site of plant nutrient and other metabolite output, providing a rich source of C and energy for nearby microorganisms ( Dakora and Phillips, 2002 ; Bulgarelli et al, 2013 ).…”
Section: Discussionsupporting
confidence: 75%